Effect of vitamin A supplementation on cause-specific mortality in women of reproductive age in Ghana: a secondary analysis from the ObaapaVitA trial - Lisa Hurt; Augustinus ten Asbroek; Seeba Amenga-Etego; Charles Zandoh; Samuel Danso; Karen Edmond; Chris Hurt; Charlotte Tawiah; Zelee Hill; Justin Fenty; Seth Owusu-Agyei; Oona M Campbell; et al. (The World Health Organization, 2013)
OBJECTIVE: To determine the effect of weekly low-dose vitamin A supplementation on cause-specific mortality in women of reproductive age in Ghana. METHODS: A cluster-randomized, triple-blind, placebo-controlled trial was conducted in seven districts of the Brong Ahafo region of Ghana. Women aged 15-45 years who were capable of giving informed consent and intended to live in the trial area for at least 3 months were enrolled and randomly assigned, according to their cluster of residence, to receive oral vitamin A (7500 Âµg) or placebo once a week. Randomization was blocked, with two clusters in each fieldwork area allocated to vitamin A and two to placebo. Every 4 weeks, fieldworkers distributed capsules and collected data during home visits. Verbal autopsies were conducted by field supervisors and reviewed by physicians, who assigned a cause of death. Cause-specific mortality rates in both arms were compared by means of random-effects Poisson regression models to allow for the cluster randomization. Analysis was by intention-to-treat, based on cluster of residence, with women eligible for inclusion once they had consistently received the supplement or placebo capsules for 6 months. FINDINGS: The analysis was based on 581 870 woman-years and 2624 deaths. Cause-specific mortality rates were found to be similar in the two study arms. CONCLUSION: Low-dose vitamin A supplements administered weekly are of no benefit in programmes to reduce mortality in women of childbearing age.